Aplicación de la NIIF 6 en los registros contables en un proyecto minero en el Ecuador. - Arreaga Martinez, Rosa Angelica (My University, 2019)
The research work addresses one of the topics of current interest, precisely speaking about mining exploration in Ecuador and how it contributes significantly to the economic and social development of those involved, for this purpose the objective of this research is to analyze the IFRS 6 and based on this, propose an exercise that denotes the accounting entries in the exploration stage, their accounting treatment becomes of relative importance in the study since it is directly related to the Exploration and evaluation of mineral resources that has been adopted in several countries of the world and whose main benefit is that it allows to better control the investments required by the exploration of minerals and on the other hand that their information is accepted in international markets, being able to attract the attention of new investors; in its relevant part, the user will be able to find the theoretical references that speak about accounting, the mining sector and international accounting regulations, then he will be able to observe the practical development that derives in final conclusions that become a starting point for new related investigations .
El trabajo investigativo aborda uno de los temas de interés actuales, precisamente se habla de la exploración minera en el Ecuador y cómo esta contribuye de manera significativa al desarrollo económico y social de los involucrados, para ello el objetivo de la presente investigación es aplicar la Niif 6 en los registros contables en un proyecto minero en el Ecuador, su tratamiento contable cobra una importancia relativa en el estudio ya que se lo relaciona directamente con la Exploración y evaluación de recursos minerales que ha sido adoptada en varios países del mundo y cuyo beneficio principal es que permite controla de mejor forma las inversiones que requiere la explotación de los minerales y por otra que su información es aceptada en mercados internacionales, pudiendo atraer la atención de nuevos inversionistas; en su parte pertinente el usuario podrá encontrar los referentes teóricos que hablan acerca de la contabilidad, el sector minero y la normativa contable internacional, seguidamente podrá observar el desarrollo práctico que deriva en conclusiones finales que se convierten en un punto de partida para nuevas investigaciones relacionadas.
Keywords: NIIF 6; PROYECTO MINERO; EXPLORACIÓN; RECURSOS NO RENOVABLES; ECUADOR